Characteristics of Knowledge Economy in Respect of Hungary - T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2016)
The examination of the economic role of information, knowledge, human capital and investment into the human capital has come into the limelight over the last decades. Analyses include the characterisation of knowledge economy and the relationship between knowledge economy and market challenges. In this paper we examine the definition and indicators of knowledge-based economy. We analyse the trend of the participation rate in formal and non-formal education as a knowledge input, furthermore we examine the gross domestic expenditure on R&D as a percentage of GDP with particular attention to Hungary.